2023
DOI: 10.3390/atmos14030483
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Rainfall and Temperature Extremes in Ethiopia: Station and Agro-Ecological Zone Levels of Analysis

Abstract: Climate extreme events have been observed more frequently since the 1970s throughout Ethiopia, which adversely affects the socio-economic development of the country, as its economy depends on agriculture, which, in turn, relies heavily on annual and seasonal rainfall. Climate extremes studies conducted in Ethiopia are mainly limited to a specific location or watershed, making it difficult to have insights at the national level. The present study thus aims to examine the observed climate extreme events in Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, R95p showed a decreasing significant trend for Bele and Areka. This is incongruent with Wubaye et al [ 11 ] in which rainfall showed a downward significant trend in many of the gauge stations. The temperature indices showed the overall warming trend over the Ghibe III Dam watershed.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, R95p showed a decreasing significant trend for Bele and Areka. This is incongruent with Wubaye et al [ 11 ] in which rainfall showed a downward significant trend in many of the gauge stations. The temperature indices showed the overall warming trend over the Ghibe III Dam watershed.…”
Section: Discussioncontrasting
confidence: 81%
“…Grounding climate variability study on the extreme theory helps to understand the extent, magnitude, probability, characteristics, and frequency of climate extremes so that understanding can be reached to develop better adaptation strategies and actions to be taken on the extreme events happening. Nevertheless, Jothimani et al and Wubaye et al [ 10 , 11 ] showed that the extremes of climate caused by variability have not been the focus of many studies in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Humanitarian crises in Ethiopia are often associated with drought, armed conflict, pest outbreaks, and political instability, of which drought is a main factor reducing agricultural production and increasing malnutrition among the affected communities (Alasow et al, 2023; CDP, 2023; Wubaye et al, 2023) (Figure 1, II). The frequency of droughts affecting cropland in Ethiopia has nearly doubled in the last 50 years (Alasow et al, 2023) and the severe drought that began in 2020 has continued into 2023, with Ethiopia enduring five failed rainy seasons (Alasow et al, 2023; CDP, 2023; Wubaye et al, 2023). In addition to drought, Ethiopia has experienced several armed conflicts, including the Tigray civil conflict, and disputes between the Ethiopian military and the militias in Amhara, creating a dire situation for more than five million people across these regions (CDP, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies argue that the microclimate pattern of developing cities is unique in their climates, vulnerabilities, and exposures, which has significance for cities' climate adaptation strategies (Filho et al 2019, Wubaye et al 2023. Hence, the urban environment has spatial heterogeneous characteristics, and the impact of changing conditions and responses varies in time and location.…”
Section: Introductionmentioning
confidence: 99%